The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3390/su10020434
|View full text |Cite
|
Sign up to set email alerts
|

Greenway Implementation Influence on Agricultural Heritage Sites (AHS): The Case of Liantang Village of Zengcheng District, Guangzhou City, China

Abstract: Abstract:As environment-friendly recreational facilities, greenways can bring ecological, social, and economic benefits to the residents of agricultural heritage sites (AHS). Zengcheng District of Guangzhou City first implemented the recreational greenway in China in 2008. Liantang Village is the tourist center of the Liantang Spring segment of Zeng River Greenway system. This village has always been an important planting region of black olive and lychee from ancient times, with more than 1800 large old trees … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 29 publications
(32 reference statements)
1
6
0
Order By: Relevance
“…From the multiple regression analysis, we found that greenway trail characteristics including trail width, trail surface, amount of vegetation, background buildings, built structures, and adjacent automobile traffic on trails were significant predictors of likability. Previous studies have consistently shown that natural elements such as vegetation have a positive interaction with the greenway trail environment [14][15][16]30]. This study also provided evidence to support that vegetation was significant in relation to likability, as shown in the literature.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…From the multiple regression analysis, we found that greenway trail characteristics including trail width, trail surface, amount of vegetation, background buildings, built structures, and adjacent automobile traffic on trails were significant predictors of likability. Previous studies have consistently shown that natural elements such as vegetation have a positive interaction with the greenway trail environment [14][15][16]30]. This study also provided evidence to support that vegetation was significant in relation to likability, as shown in the literature.…”
Section: Discussionsupporting
confidence: 82%
“…In addition, greenways have not only captured attention due to connecting urban ecosystems [7] but, from a social perspective, are also recognized as places for recreation and as areas that maintain the scenic quality of the landscapes in urban areas [8]. In other words, greenways provide benefits to individuals in the form of scenic views and access to a variety of experiences related to health, recreation, alternative transportation, and tourism at the community level (e.g., [3,5,[8][9][10][11][12][13][14]). Many studies have examined human interactions with the natural environment, especially greenways, due to the benefits that such interactions offer [15][16][17][18], and thus, "an affective state is an important indicator of the nature and significance of a person's ongoing interaction with an environment" [19].…”
mentioning
confidence: 99%
“…Adequate environment, plentiful biological resources, and unique regional features of agricultural heritage system sites ensure the nutrition and food safety for local residents and inhabitants, and give the landscape an aesthetic appeal [32], all of which are conducive to the development of additional economic activity to increase farmers' incomes [33]. Most agricultural heritage systems are in areas of poverty that lack modern technology, so how to transform resources into income for local inhabitants is an urgent issue.…”
Section: Multi-values Of China-niahsmentioning
confidence: 99%
“…In the PRD, there have been long-term debates on the function, form and policies of the PRD greenways in China. A few researches have investigated the perception of flagship greenway projects, such as Wutong Greenway [13] and Liantang Village [4,17]. However, whether the perception of the flagship projects can present the overall greenway network is still overlooked, considering the diverse function and forms of greenways in the PRD.…”
Section: Discussionmentioning
confidence: 99%
“…In the PRD, over 12,500 kilometers of greenways have been rapidly implemented during the last decade as the result of a regional policy aiming to achieve social, economic, and ecological benefits [4]. For this emerging greenway network in the largest metropolitan area in the world, there is a growing body of research on the regional governance [10][11][12], usage patterns [13][14][15], quality of the space [16], and rural economy [17]. However, little research has been conducted to understand the public perception of greenways, especially at the regional scale.…”
Section: Introductionmentioning
confidence: 99%